KEPEMIMPINAN HUMANISTIK DALAM MENINGKATKAN KESEJAHTERAAN PSIKOLOGIS DAN KINERJA KARYAWAN - Zebua, Martin; Anam, Chairul (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to explain the application of humanistic leadership values and their influence on the psychological well-being and performance of employees in a spiritual-based service organisation, namely Umi Muthmainah Berkah Umrah and Haji Travel in Surabaya. This study uses a qualitative approach with a case study method to explore in depth the experiences and perceptions of leaders and employees. Data were collected through in-depth interviews, observations, and documentation, then analysed using Miles and Huberman's interactive model, which includes data reduction, presentation, and conclusion drawing. The results show that leaders apply a leadership style based on empathy, appreciation, and support for employees, thereby creating a harmonious, open, and trusting work atmosphere. Humanistic leadership has been proven to improve employees' psychological well-being, intrinsic motivation, and work loyalty. The novelty of this research lies in the integration of three main theories Humanistic Leadership, Psychological Well-Being, and Self-Determination in the context of religious service organisations, which emphasises the importance of spirituality as a reinforcing factor in the relationship between leadership and employee well-being.